Ethylene Propylene Diene Terpolymer-G-Maleic Anhydride of Paper Sludge Filled Polypropylene composites - Salmah, Husseinsyah; Che Mohd Ruzaidi, Ghazali; Supri, A. Ghani; I.Ismail (Universiti Putra Malaysia, 2010)
Organized by Universiti Putra Malaysia, 10th - 12th December 2007 at Impiana Cherating Hotel, Pahang.